Pension Wealth Uncertainty. Issue 4 (8th November 2012) - Guiso, Luigi; Jappelli, Tullio; Padula, Mario
ABSTRACT Using a representative sample of Italian investors, we measure the uncertainty of social security benefits by eliciting for each individual the subjective distribution of the replacement rate as a summary indicator of pension uncertainty. We find that pension uncertainty varies across individuals in a way that is consistent with what one would expect a priori, given different information sets and pension schemes. In particular, individuals who are a long way from retirement, and thus face more career uncertainty, report more subjective pension uncertainty. Since expectations reveal information about people's understanding of pension reforms, our findings suggest that they should also be an important determinant of how people respond to reforms.